2003
DOI: 10.1002/jbm.a.10015
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable polyurethane‐ascorbic acid scaffold for bone tissue engineering

Abstract: A novel, nontoxic, biodegradable, sponge-like polyurethane scaffold was synthesized from lysine-di-isocyanate (LDI) and glycerol. Ascorbic acid (AA) was copolymerized with LDI-glycerol. Our hypothesis was that the AA-containing polymer foam would enhance the biological activity of the osteoblastic precursor cell (OPCs). The LDI-glycerol-AA matrix degraded in aqueous solution to the nontoxic products of lysine, glycerol, and AA. The degradation products did not significantly affect the solution pH. The physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 27 publications
0
63
1
1
Order By: Relevance
“…However, in this study, the bFGF was released from a pre-formed polymer scaffold, not from a reactive polymer. PUR scaffolds prepared by reactive liquid molding of LDI, glycerol, water, and ascorbic acid (AA) have been shown to support controlled release of AA over 60 days (51). By dissolving the AA in the glycerol prior to adding the LDI, the AA was covalently bound to the polymer through reaction of the primary hydroxyl group in the AA with LDI to form urethane linkages.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the bFGF was released from a pre-formed polymer scaffold, not from a reactive polymer. PUR scaffolds prepared by reactive liquid molding of LDI, glycerol, water, and ascorbic acid (AA) have been shown to support controlled release of AA over 60 days (51). By dissolving the AA in the glycerol prior to adding the LDI, the AA was covalently bound to the polymer through reaction of the primary hydroxyl group in the AA with LDI to form urethane linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid has large impact on tissues regeneration due to improving collagen synthesis [20], which is a component of the primary extracellular matrix (ECM) [21], which supports cells attachment, growth, and proliferation [22]. Some literature data show that researchers took an attempt to incorporate AA into the polyurethane structure to improve the material biocompatibility and biodegradability [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In case of using AA as a polyurethane chain modifier, it would be also subjected to thermal treatment such as polyurethane synthesis and curing (both carried out at 80°C). Thermal stability is of particular interest, because of the thermal decomposition kinetics studies, which may lead to improvement in ascorbic acid stability, which is important especially considering the context of pharmaceuticals, food products [18], and recently medical devices, modified with ascorbic acid [23,24]. In the literature are available degradation studies of ascorbic acid, carried out under different conditions, such as in different solvents [30], in steam [31], in food [20], under oxygenated conditions [32] and under inert conditions [33].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of hard segments influences the degree of phase separation, which in turn affects physical and mechanical properties [30], degradation rate and biocompatibility [32][33]. By varying the molecular weight of polyol and the composition of the different segments, properties of PUR can be tuned up for use in many areas of TE [34][35][36][37][38]. In this respect, the range of mechanical and morphological properties that can be obtained with PUR is significantly larger than with commonly used medical grade biodegradable polymers for example: PLA, PGA, poly(DL-lactide) (PDLLA) [39][40][41][42].…”
Section: Polyurethanes In Tementioning
confidence: 99%
“…During the studies they showed that obtained LDI-glycerol-L-AA matrix degrade in aqueous solution to the nontoxic products of lysine, glycerol, and L-AA. The degradation products did not significantly affect the pH solution and physical properties [37]. Mouse osteoblastic precursor cells (OPCs), which they used to attach to the polymer matrix, remained viable.…”
Section: Ascorbic Acid Based Polyurethane Systems For Tementioning
confidence: 99%